1976
DOI: 10.1128/aac.10.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Interferon-Inducing Activity of a New Glutarimide Antibiotic, 9-Methylstreptimidone

Abstract: The antiviral effect of 9-methylstreptimidone (9-MS) was examined in mice infected with mouse-adapted influenza A2 (H2N2) virus. Both a single and continuous prophylactic administration of 9-MS protected mice from virus infection, and comparison between the minimal effective and the 50% lethal dose gave a therapeutic index of 60. When the treatment was started after infection, however, no antiviral effect was demonstrated. After a single intraperitoneal administration of 9-MS, a highly potent virus-inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…An equally strong correlation between the degree of protection and the amount of IFN in lung tissues was also obtained in our inducer studies as reported elsewhere (Suzuki et al 1975;Saito et al 1976). Among two tested inducers, dextran phosphate (DP -40) produced a larger amount of IFN in the lung than in the serum after i,p.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An equally strong correlation between the degree of protection and the amount of IFN in lung tissues was also obtained in our inducer studies as reported elsewhere (Suzuki et al 1975;Saito et al 1976). Among two tested inducers, dextran phosphate (DP -40) produced a larger amount of IFN in the lung than in the serum after i,p.…”
Section: Discussionsupporting
confidence: 90%
“…9-Methylstreptimidone, low-molecular IFN inducer, produced large amounts of IFN both in the lung and serum after i.p. injection, and also exhibited a marked anti-influenza effect (Saito et al 1976). However, as Nemes et al (1969) reported, i.p, injection of poly I:C which produced little IFN in the lung in spite of producing large amounts of circulating IFN in the blood resulted in no protective effect against influenza virus infection in mice, and the same result was obtained by us (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Ряд сообщений описывают действие экзогенного IFN против гриппозной инфек-ции [29,32]. Кроме того, во многих сообщени-ях описано противовирусное действие индук-торов IFN, таких как 9-метилстрептимидон и декстранфосфат, на гриппозную инфекцию у мышей [28,31,32,33,35,36]. Было доказано, что эти индукторы IFN проявляют свое про-тективное действие против гриппозной ин-фекции через индукцию IFN [4,33,34,36].…”
Section: иммуномодулирующая активностьunclassified
“…It inhibits the growth of poliovirus, vesicular stomatitis virus, and Newcastle disease virus in vitro and is effective in prolonging the life of mice infected with 4,5,5,5,7,7,8,8,8,8,9,9,9, influenza virus (20). Although 9-MS stimulates interferon production in mouse lung cells and serum (14,20), the mechanism of the protective action of 9-MS on influenza-infected mice has not been completely characterized. Whereas the protective effect of 9-MS against influenza virus infection in vivo is obtained with a nontoxic dose, it inhibits growth of influenza virus in vitro only when present at almost cytotoxic concentrations.…”
mentioning
confidence: 99%